Growth and Spectral Properties of Er3+ and Yb3+ Co-Doped Bismuth Silicate Single Crystal - Yan Zhang; Shucheng Hu; Tian Tian; Xuefeng Xiao; Yuanzhi Chen; Yan Zhang; Jiayue Xu (Crystals, 2022)
Rare-earth-doped bismuth silicate (Bi4Si3O12, BSO) crystal is a multifunctional material for scintillation, LED, and laser applications. In the present study, Er3+ and Yb3+ ions co-doped bismuth silicate crystals were grown by a modified vertical Bridgman method, and their spectral properties were investigated for the first time. Transparent Er/Yb: BSO single crystal up to Φ 25 mm × 30 mm was obtained. The segregation coefficient of the Er/Yb: BSO crystal was measured to be 0.96 for Er3+ ions and 0.91 for Yb3+ ions. Absorption and fluorescence spectra had been recorded in the range of 200–1700 nm. The absorption cross section was calculated to be 6.96 × 10−20 cm2 at 976 nm with the full width at half maximum (FWHM) of 8 nm, and the emission cross section was 0.9771 × 10−20 cm2 at 1543 nm with FWHM of 16 nm. The fluorescence decay curve was measured at 976 nm excitation. By linear fitting, the fluorescence lifetime of the upper 4I13/2 level of Er3+ was 8.464 ms at room temperature. Compared with Er3+ ion-doped bismuth silicate crystal (Er: BSO), the Er/Yb: BSO crystal has a wider FWHM and larger absorption cross section. The results indicate that the Er/Yb: BSO crystal is a potential lasing crystal.